9x+8.86=x+11

Simple and best practice solution for 9x+8.86=x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+8.86=x+11 equation:


Simplifying
9x + 8.86 = 0

Reorder the terms:
8.86 + 9x = 0

Solving
8.86 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8.86' to each side of the equation.
8.86 + -8.86 + 9x = 0 + -8.86

Combine like terms: 8.86 + -8.86 = 0.00
0.00 + 9x = 0 + -8.86
9x = 0 + -8.86

Combine like terms: 0 + -8.86 = -8.86
9x = -8.86

Divide each side by '9'.
x = -0.9844444444

Simplifying
x = -0.9844444444

See similar equations:

| 1/7-1/2y=1/5 | | (17/30)/(17) | | 10.8-0.2*18=x | | 2x+120=300 | | 600=15x+5y | | 5=(170-50)/(20-x) | | 8=-2(3p-3)+2(1+2p) | | -90x+-45=45x+45 | | 6=(170-50)/(20-x) | | -14x-5=65 | | 2=8-6 | | -24=2(n+3)-2(3-3n) | | -10x-2=38 | | 2x+80=250 | | -3(x-2)+3(1+2x)=0 | | -2(m+7)=-2 | | 2(3+3n)-2(1+2n)=4 | | 3(2x-8)-10=2(x+1) | | e^2x+7=11 | | -2(2+2n)+3(n-1)=-6 | | -28=2(1+3n)-(3-3n) | | -9x^3y+4x^3y+5xy= | | (4x-20)+(x+12)+(x+1)=59 | | 5=3(-1-x)+2(x+3) | | 6=-3(1+p)+2(3+2p) | | -11+8x=5x+40 | | 25/4-2 | | (-1y+5x)5= | | 16=2(n-3)+2(2n+2) | | -3(3+x)+2(3x+1)=2 | | -39=3(-3m-3)-m | | 2x+(48-9c)-c=-2 |

Equations solver categories